(untitled) (Transport systems and technologies, 2019)
The problems of professional-technological decline are described in the management of Ukrzaliznytsia JSC. There is a lack of a strategic and systematic approach to the formation senior management employees of railway enterprises. A technique is proposed for determining the labor potential of an organization over time. Universal criteria for the growth of labor potential are developed.